2015
DOI: 10.1074/jbc.m115.642314
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a WWP1/Tiul1 Tumor-derived Mutant Reveals a Paradigm of Its Constitutive Activation in Human Cancer

Abstract: Background: WWP1/Tiul1 plays an instrumental role in cancer pathogenesis by restricting TGF␤ cytostatic signaling. Results: We identified a novel mechanism of inhibition of WWP1 that is disrupted by a tumor mutation found in prostate cancer. Conclusion: Mutational activation of WWP1 contributes to the loss of TGF␤ signaling in cancer. Significance: Our data unveil a paradigm behind WWP1 hyperactivation in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…We speculate that mutating the loop residues into alanine might affect the relative positioning of critical residues which could be involved in the E2-E3 transthiolation step thus altering the UBE3C E3 ligase enzymatic activity. Functional analysis of WWP1 E3 ligase (NEDD4 HECT subfamily) showed that mutation of its conserved glutamic acid to valine (E798V) substantially increased its autoubiquitination activity in human prostate cancer [43]. The UBE3C HECT E3 ligase has an N-lobe glutamine residue (Q961) in the equivalent position, and we show that mutations of Gln961 (Q961A and Q961E) significantly reduce autoubiquitination activity ( Figure 6D,E).…”
Section: Discussionmentioning
confidence: 69%
“…We speculate that mutating the loop residues into alanine might affect the relative positioning of critical residues which could be involved in the E2-E3 transthiolation step thus altering the UBE3C E3 ligase enzymatic activity. Functional analysis of WWP1 E3 ligase (NEDD4 HECT subfamily) showed that mutation of its conserved glutamic acid to valine (E798V) substantially increased its autoubiquitination activity in human prostate cancer [43]. The UBE3C HECT E3 ligase has an N-lobe glutamine residue (Q961) in the equivalent position, and we show that mutations of Gln961 (Q961A and Q961E) significantly reduce autoubiquitination activity ( Figure 6D,E).…”
Section: Discussionmentioning
confidence: 69%
“…By analogy with the crystal structure of the related WWP1 HECT, which shows a compact and inactive conformation, this arginine is predicted to lie at the interface between the N lobe and C lobe (electronic supplementary material, figure S1). A natural mutation of WWP1 found in cancer cells maps to a similar interface location, though on an adjacent helix, and has been shown to cause constitutive activation of activity [ 32 ], perhaps by destabilizing this inactive conformation. As expected from this, we found that the arginine mutations in WWP2 partially relieved its autoinhibition, rendering it less dependent on Dvl2.…”
Section: Resultsmentioning
confidence: 99%
“…KLF2, which includes 355 amino acids, has an automatic suppression region in its first 110-167 amino acids that is capable of binding to the ubiquitin ligase WW domain. This domain contains E3 ubiquitin protein ligase 1 (WWP1), and binding leads to KLF2 protein ubiquitination and degradation [19, 20]. Studies indicate that KLF2 can activate endothelial inflammation by upregulating the expression of endothelial nitric oxides (eNOs) through the NF-kB pathway [21, 22].…”
Section: Introductionmentioning
confidence: 99%